Canyon catastrophe - Perlman, Rhea.; Santat, Dan (New York : Katherine Tegen Books, 2006)
With the help of his aunts and his trusty racecar, undercover agent Otto Pillip sets out to stop a criminal from blowing up the Grand Canyon. Includes words spelled backwards, anagrams, and palindromes.
Keywords: Spies -- Fiction; Aunts -- Fiction; Automobiles, Racing -- Fiction; Word games -- Fiction; Humorous stories; Grand Canyon (Ariz.) -- Fiction